2017
DOI: 10.1002/osp4.97
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative stress in atherosclerosis development in subjects with sarcopenic obesity

Abstract: SummaryIntroductionCo‐existing decreased muscle mass and increased visceral fat, an age‐associated change called sarcopenic obesity, results in fragility and cardiovascular disease. To assess the pathogenesis of sarcopenic obesity, we assessed the associations of clinical parameters with psoas muscle mass in elderly male subjects with obesity and type 2 diabetes.MethodsThe subjects were 55 patients, over 65 years of age and with a visceral fat area exceeding 100 cm2, with type 2 diabetes. The cross‐sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…These findings confirm that Os is related to SO [148]. Also, systemic Os is associated with a decline in muscle mass in elderly patients with obesity and T2DM [149]. Furthermore, a study identified biomarkers of inflammation and Os, such as serum adiponectin, the erythrocyte sedimentation rate (ESR), and CRP levels, as being associated with sarcopenia [150].…”
Section: Patientssupporting
confidence: 56%
“…These findings confirm that Os is related to SO [148]. Also, systemic Os is associated with a decline in muscle mass in elderly patients with obesity and T2DM [149]. Furthermore, a study identified biomarkers of inflammation and Os, such as serum adiponectin, the erythrocyte sedimentation rate (ESR), and CRP levels, as being associated with sarcopenia [150].…”
Section: Patientssupporting
confidence: 56%
“…The total CACS were analyzed according to the Agatston method [ 15 ] and were determined as previously reported [ 17 ]. The volume of abdominal fat, divided into visceral fat area and subcutaneous fat area, was obtained from CT images scanned at the level of the fourth lumbar vertebra [ 18 ]. Hepatic steatosis was defined as a liver to spleen density ratio below 0.9, based on plain abdominal CT [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lipids gradually accumulate in the arterial smooth muscle cells in the vascular smooth muscle, leading to intimal hyperplasia and plaque formation. Inflammation and oxidative stress lead to plaque rupture and arterial invasion, blockage of the lumen by thrombosis and ischemic cerebral infarction [23,24]. Thus, there is a complementary relationship between the level of inflammation and carotid atherosclerotic plaque formation.…”
Section: Discussionmentioning
confidence: 99%